Ecological interactions shape the evolution of flower color in communities across a temperate biodiversity hotspot. Issue 3 (1st June 2021) - Skeels, Alexander; Dinnage, Russell; Medina, Iliana; Cardillo, Marcel
Abstract: Processes driving the divergence of floral traits may be integral to the extraordinary richness of flowering plants and the assembly of diverse plant communities. Several models of pollinator-mediated floral evolution have been proposed; floral divergence may (i) be directly involved in driving speciation or may occur after speciation driven by (ii) drift or local adaptation in allopatry or (iii) negative interactions between species in sympatry. Here, we generate predictions for patterns of trait divergence and community assembly expected under these three models, and test these predictions in Hakea (Proteaceae), a diverse genus in the Southwest Australian biodiversity hotspot. We quantified functional richness for two key floral traits (pistil length and flower color), as well as phylogenetic distances between species, across ecological communities, and compared these to patterns generated from null models of community assembly. We also estimated the statistical relationship between rates of trait evolution and lineage diversification across the phylogeny. Patterns of community assembly suggest that flower color, but not floral phenology or morphology, or phylogenetic relatedness, is more divergent in communities than expected. Rates of lineage diversification and flower color evolution were negatively correlated across the phylogeny and rates of flower colour evolution were positively related to branching times. These results support a role for diversity-dependent species interactions driving floral divergence during the Hakea radiation, contributing to the development of the extraordinary species richness of southwest Australia.